2001
DOI: 10.1097/00007632-200103150-00015
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fusion Rates With Cervical Plating for Three-Level Anterior Cervical Discectomy and Fusion

Abstract: The addition of plate fixation for three-level anterior cervical discectomy and fusion is a safe procedure and does not result in higher complication rates. In this study, the pseudarthrosis rate was lower for patients with a cervical plate. However, this difference was not statistically significant. Patients treated with cervical plating had overall better results when compared with those of patients treated without cervical plates. Although the use of cervical plates decreased the pseudarthrosis rate, a thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(122 citation statements)
references
References 19 publications
6
112
0
4
Order By: Relevance
“…19 However, multilevel fusions are associated with high pseudarthrosis rates, iliac crest donor site morbidity, persistent postoperative dysphagia, and the development of adjacent-level degeneration and disease. 2,8,11,17,20 Arthroplasty may be the solution to these comorbidities. Sekhon 15 was the first to report that cervical arthroplasty in the setting of cervical myelopathy was a safe and excellent alternative to fusion.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, multilevel fusions are associated with high pseudarthrosis rates, iliac crest donor site morbidity, persistent postoperative dysphagia, and the development of adjacent-level degeneration and disease. 2,8,11,17,20 Arthroplasty may be the solution to these comorbidities. Sekhon 15 was the first to report that cervical arthroplasty in the setting of cervical myelopathy was a safe and excellent alternative to fusion.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,13,15,17,18,20 Despite the widespread application of anterior plates, clinicians have not been able to eliminate the development of pseudarthrosis. 11,24,25 Complaints associated with a cervical nonunion include persistent or recurrent axial neck pain, radiculopathy, and myelopathy. Development of a pseudarthrosis has also been associated with kyphotic deformity, potentially leading to pain and neurological deficits.…”
Section: Rationalementioning
confidence: 99%
“…Numerous published studies have shown considerable variation in the incidence of non-union. The lowest rates (3-20%) are reported in patients after singlelevel procedures [2,8,12,16,19,22,26,27,29,30], while the incidence of pseudoarthrosis increases to 44% with a greater number of levels fused [4,12,16,22,26,27,30,34,35,36,38,39].…”
Section: Petr Suchomel Pavel Barsa Pavel Buchvald Adam Svobodnik Eva mentioning
confidence: 99%
“…The lower fusion rates have been attributed to the increased amount of graft material and number of interfaces that must be consolidated with multi-level surgery, as well as the increased compressive loads on the multiple graft sites resulting in micro-motions [35]. Although non-fusion is not typically associated with poor clinical outcomes, its significant role in postoperative morbidity is well documented [4,5,10,14,23].…”
Section: Petr Suchomel Pavel Barsa Pavel Buchvald Adam Svobodnik Eva mentioning
confidence: 99%